2023
DOI: 10.1093/humrep/dead135
|View full text |Cite
|
Sign up to set email alerts
|

Should we perform oocyte accumulation to preserve fertility in women with Turner syndrome? A multicenter study and systematic review of the literature

Abstract: STUDY QUESTION Should we perform oocyte accumulation to preserve fertility in women with Turner syndrome (TS)? SUMMARY ANSWER The oocyte cryopreservation strategy is not well adapted for all TS women as their combination of high basal FSH with low basal AMH and low percentage of 46,XX cells in the karyotype significantly reduces the chances of freezing sufficient mature oocytes for fertility preservation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The median number of vitrified oocytes in the first stimulation cycle in women with TS is in line with other studies that reported a mean/median of 4-9 vitrified oocytes per cycle [13][14][15]. Compared to women who cryopreserve oocytes before the start of an oncological treatment (mean 9.5 ± 6.1 oocytes per cycle), the number of vitrified oocytes per cycle is generally lower in women with TS due to the accelerated loss of follicles at a young age [2,18].…”
Section: Interpretation Of the Findingssupporting
confidence: 91%
See 4 more Smart Citations
“…The median number of vitrified oocytes in the first stimulation cycle in women with TS is in line with other studies that reported a mean/median of 4-9 vitrified oocytes per cycle [13][14][15]. Compared to women who cryopreserve oocytes before the start of an oncological treatment (mean 9.5 ± 6.1 oocytes per cycle), the number of vitrified oocytes per cycle is generally lower in women with TS due to the accelerated loss of follicles at a young age [2,18].…”
Section: Interpretation Of the Findingssupporting
confidence: 91%
“…Our results are largely consistent with previous studies that have reported on vitrification outcomes in women with TS [13][14][15]. The majority of ovarian stimulations and oocyte retrievals were performed safely, as complications only occurred after 3/69 punctures.…”
Section: Interpretation Of the Findingssupporting
confidence: 91%
See 3 more Smart Citations